2016
DOI: 10.1016/j.agee.2016.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Approaches and mechanisms for ecologically based pest management across multiple scales

Abstract: A B S T R A C TThe past 50 years have seen substantial change of agroecosystems in the world, including an intensified use of agrochemicals and expansion of cropland, resulting in a rapid loss of biodiversity and a reduction of ecosystem services. The effects of these changes, at both the field and landscape scale, on ecologically based pest management (EBPM) in agroecosystems have become increasingly important. Here, we review the theories, important approaches and mechanisms of habitat management practices (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 159 publications
(190 reference statements)
0
24
0
2
Order By: Relevance
“…A. baccarum is a habitat generalist, it lays eggs in a wide variety of habitats, including tea canopies, litter, and cover crop vegetation, and therefore it is unlikely to be directly influenced by available extra habitat. On the other hand, intercropping cover crops may provide an increased amount of food sources and, likely, also a greater protection from predators . This theory is supported by the fact that the treatment effect was more pronounced in tea canopies than it was in cover crop vegetation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A. baccarum is a habitat generalist, it lays eggs in a wide variety of habitats, including tea canopies, litter, and cover crop vegetation, and therefore it is unlikely to be directly influenced by available extra habitat. On the other hand, intercropping cover crops may provide an increased amount of food sources and, likely, also a greater protection from predators . This theory is supported by the fact that the treatment effect was more pronounced in tea canopies than it was in cover crop vegetation.…”
Section: Discussionmentioning
confidence: 94%
“…One such strategy may be intercropping the rows with beneficial plants; a common practice for ecological engineering. In theory, greater botanical diversity in an intercropped tea plantation system, along with a higher number of available niches, can support greater diversity of invertebrate species than that with cleared rows . However, diverse, naturally grown, weedy vegetation between tea rows may compete with tea for resources and its growth may be difficult to control.…”
Section: Introductionmentioning
confidence: 99%
“…Although they can be implemented at the farm level, they together induce a diversification at the landscape scale, influencing insects (both pests and natural enemies) that are highly mobile, easily crossing farm borders. Hence, considering the landscape scale, in addition to smaller scales, is essential to understand the pest regulation processes and to design pest control strategies (Tscharntke et al, 2005;Zhao et al, 2016). These last 10 years, studies highlighted how spatial diversification of agroecosystems can lead to the regulation of insect pests.…”
Section: Introductionmentioning
confidence: 99%
“…We used habitats (woodlots and fallow lands) that have positive effects on ladybeetle abundance to define landscape complexity in order to provide a more accurate measure of the effects of landscape complexity on ladybeetles in the studied region . Our results indicated that ladybeetle abundance was significantly lower in wheat fields exposed to higher insecticide pressure, regardless of how complex or simple the landscape was, even though previous studies have suggested that a large positive contribution by non‐crop habitats in a complex landscape can provide more abundant resources and refuges for ladybeetles, and would be able to better mitigate the negative effects of insecticide use in crop fields . Although complex landscapes promoted ladybeetle occurrence in wheat fields, the negative effects of higher insecticide stress on ladybeetles, which have a high dispersal ability and can escape insecticides and recolonize wheat fields easily, were not fully offset even in the complex landscape.…”
Section: Discussionmentioning
confidence: 75%
“…49 Our results indicated that ladybeetle abundance was significantly lower in wheat fields exposed to higher insecticide pressure, regardless of how complex or simple the landscape was, even though previous studies have suggested that a large positive contribution by non-crop habitats in a complex landscape can provide more abundant resources and refuges for ladybeetles, and would be able to better mitigate the negative effects of insecticide use in crop fields. 2,10,31,64 Although complex landscapes promoted ladybeetle occurrence in wheat fields, the negative effects of higher insecticide stress on ladybeetles, which have a high dispersal ability and can escape insecticides and recolonize wheat fields easily, were not fully offset even in the complex landscape. We explain this phenomenon in three ways: (i) the population abundance of ladybeetles in non-crop habitats was not large enough to offset the reduction caused by insecticide use; (ii) there was not enough time for ladybeetles to recolonize the wheat field during the relatively short growing period; or (iii) ladybeetles prefer to forage and reproduce in non-crop habitats, which have sufficient resources, rather than in wheat fields after insecticide application, where prey may be temporarily scarce.…”
Section: Discussionmentioning
confidence: 99%